1997
DOI: 10.2337/diacare.20.11.1706
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Plantar Pressure in the Neuropathic Foot: A comparison of footwear

Abstract: When used in conjunction with a viscoelastic insole, both the comfort and athletic cross-trainer shoes studied were as, if not more, effective than commonly prescribed therapeutic shoes in reducing mean peak first and lesser metatarsal pressures. Furthermore, comfort shoes were as effective as therapeutic shoes in reducing pressure under the great toe. Both of these shoe types may be viable options to prevent the development or recurrence of foot ulcers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
1
7

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(82 citation statements)
references
References 11 publications
1
72
1
7
Order By: Relevance
“…Several studies have found that increased contact area reduces plantar pressure in the forefoot by 35-44% (3,4,(13)(14)(15)(16)(17). Although in our study the use of an individualized EVA insole inside an Xtra depth shoe increased the effective contact area between foot and insole, this did not result in significant pressure reductions underneath the forefoot.…”
Section: Vas Scorescontrasting
confidence: 46%
“…Several studies have found that increased contact area reduces plantar pressure in the forefoot by 35-44% (3,4,(13)(14)(15)(16)(17). Although in our study the use of an individualized EVA insole inside an Xtra depth shoe increased the effective contact area between foot and insole, this did not result in significant pressure reductions underneath the forefoot.…”
Section: Vas Scorescontrasting
confidence: 46%
“…A avaliação dos pés constitui-se em passo fundamental na identificação dos fatores de risco que podem ser modificados, o que, conseqüen-temente, reduzirá o risco de ulceração e amputação de membros inferiores nas pessoas com diabetes (30) . Autores destacam que a diminuição da sensação protetora, caracterizada pela redução da sensação dolorosa de trauma na pele (3,(32)(33)(34)(35)(36)(37) , bem como a ausência parcial ou total do reflexo Aquileu (14,26,(38)(39) constituem sinais precoces de futuros processos ulcerativos nos pés, significando alto risco para o desenvolvimento de complicações. Ambas as alterações podem ser avaliadas mediante testes que utilizam vários tipos de instrumentos, desde os mais sofisticados aos mais simples.…”
Section: Avaliação Dos Pés E Prevenção De Complicaçõesunclassified
“…Dentre essas intervenções, salienta-se o uso constante de calçados apropriados de acordo com a necessidade de cada pessoa. Estudos apontam que os pontos de alta pressão, calosidades, deformidades nos pés, amputação de dedos, ou mesmo transmetatarsianos, são problemas que podem ser corrigidos com calçados confortáveis ou confeccionados sob medida, coadjuvados com palmilhas (9,(20)(21)25,30,34,37,46) . Estudo prospectivo, realizado em hospital de ensino para avaliar pessoas com diabetes de alto risco, identificou menor recorrência de ulcerações no grupo que havia recebido calçados especialmente confeccionados (55) .…”
Section: Avaliação Dos Pés E Prevenção De Complicaçõesunclassified
“…Four articles were about use of shoes with insoles and its effect on plantar pressure; that 2 of them were RCT [25,26], and 2 cohort studies [27,28]. Four articles examined the effect of rocker in shoes on the plantar pressure in which 2 articles were case control [29,30], 1 RCT [31], and 1 article review [32].…”
Section: Plantar Pressurementioning
confidence: 99%